Enhancing security in wireless multicasting with selective precoding. (2015) - Giti, J.E.; Chowdhury, S.A.H.; Ali, M.M.
We consider the problem of secure wireless multicasting through multiple-input multiple-output (MIMO) radio system in which two co-existing users communicate with two groups of receivers in the presence of multiple eavesdroppers. At first, we calculate the secrecy multicast capacity of each group and investigate the impact of interferences on it. We also quantify the loss of secrecy multicast capacity due to interferences. Then, we use zero-forcing (ZF) precoding at a relay to enhance the secrecy multicast capacity of each group by eliminating interferences. Finally, we propose a scheme to improve the secrecy multicast capacity of each group making use of interference energy that already exists in the communication medium employing selective precoding at the relay. In the proposed scheme, interference provides an additional source of energy that enhances secrecy multicast capacity at each group without the need to increase the transmitted power. Our results show that exploiting free interference power, the performance of co-existing wireless multicasting can be improved without affecting the performance of each other.